The Correlation of Motivation and Habit with Learning Outcomes in New Normal Era - Muhammad Indra; Sudji Munadi; Tika Widari (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
This article explores the relationship between learning motivation, learning habit, and the learning outcomes of grade 11th class vocational school students in the practice of lathe machining in the new normal era. This study uses a quantitative approach with research subjects in vocational schools in the field of mechanical engineering expertise. Data collection using questionnaires, tests, and documentation. Pearson Product Moment correlation analysis technique, t-test, and F test, using SPSS software. The results of this study are divided into two, namely: single regression and multiple regression will be explained as follows. 1) Single regression includes: a) learning motivation variable with learning outcomes (R) value of 0.465, value (r2) of 0.217 meaning that there is a relationship with the medium category of learning motivation with learning outcomes, (b) learning habit with learning outcomes (R) value of 0.484, the value (r2) is 0.235, meaning that there is a relationship with the medium category between learning motivation and learning outcomes. 2) Multiple regression between the variables of learning motivation and learning habit simultaneously provides a positive and significant relationship with learning outcomes. This is indicated by the value (R) of 0.550, and the value (r2) is 0.302 which means that there is a relationship with a moderate category between learning motivation and learning habit on the learning outcomes of vocational school students in the practice of lathe machining grade 11th class in the new normal era. The limitations and implications of the research will be discussed in more detail in the discussion. Keywords: Learning Motivation, Learning Habit, Learning Outcomes